The Dynamics of Gender-Based Violence Through Generative Technology (Deepfake & Voice Cloning) in a Digital Communication Perspective - Ilmi Sila Ayu; Febi Ramadhani Rusdin; Muhammad Taslim (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The proliferation of generative Artificial Intelligence (AI) technologies has transformed the digital communication landscape, while simultaneously emerging new variants of online gender-based violence (OGBV). This study aims to analyze how deepfake and voice cloning technologies are utilized as instruments of symbolic terror, blurring the lines between reality and fabrication. Employing a qualitative approach with case study methods and critical discourse analysis, this research examines the phenomenon of AI misuse within the context of Computer-Mediated Communication (CMC). The findings indicate that AI-facilitated violence creates a